Design and fabricate a speed reducer gearbox - Mohd Arif, Mohd Ariffin (2008)
The idea to create and build a Speed reducer gearbox is come from supervisor that gives me this title and task for this project. The purpose to design and fabricated this speed reducer for reduce speed from motor and transfer to differential at suitable speed. First, get an idea from reference book, internet and other from available data. Form there the information and idea to design and fabricated can be created. Whole project involves various methods such as collecting data, concept design and fabrication process. The whole project involved various method and process that usually use in engineering such as concept design, analysis process and lastly fabrication process. This final year project takes one semester to complete. This project is individual project and must be done within this semester. In this project, students must able apply all knowledge during their studies in this Diploma of Mechanical Engineering course. Overall from this project, time management and discipline is important to make sure this roject goes smooth as plan and done at correct time.